THE MERAUKE–SINGAPORE CROCODILE SKIN TRADE NETWORK DURING THE DUTCH COLONIAL PERIOD - Kulyasin Kulyasin; Alim Mutaqin; Ade Sopyan Hadi; Fikstif Donal Lintong (SOSIOEDUKASI, 2026)
This article examines the crocodile skin trade network that operated between Merauke the southernmost district of Dutch New Guinea (Nederlands Nieuw-Guinea) and Singapore as the principal entrepôt port of Southeast Asia during the Dutch colonial period, approximately from the early twentieth century until the territory's transfer to the United Nations in 1962. Drawing on Dutch colonial archives, marine biology reports, and international literature on the exotic skin trade, this article argues that the commodification of crocodile hides in Merauke constituted part of a broader system of natural resource exploitation linking colonial peripheries in Papua to European luxury markets via Singapore as a redistributive node. The Dutch trading company IMEX (Import en Export Maatschappij) emerged as a key actor integrating local hunters of the Marind-anim and Asmat peoples into global commodity chains. The article further demonstrates that large-scale unregulated hunting imposed serious ecological pressure on saltwater crocodile (Crocodylus porosus) populations in the region, planting the seeds of conservation discourse that emerged at the twilight of the colonial era.